Environment understanding during walking via modality conversion from visual to haptic information: evaluate impression for the vibro-stimuli simulated by optical flow - Morita, Shinichiro; Endo, Itta; Kobayashi, Harumi; Mukawa, Naoki; Nakamura, Akio (SPIE, 2021)
The purpose of this research is to propose the method providing visually impaired users with environment understanding via haptic vibration information. According to studies on ecological perception, optical flow, which represents dynamical visual variation, plays a significant role in environment understanding for humans. We have developed a head-mounted wearable device equipped with a 2-dimensional distance sensor and five vibro-motors arranged around the head. The vibration magnitude of vibro-motors is defined as not only a static distance to an obstacle but also dynamic distance variation caused by the user movement. The vibro-stimuli are generated based on the optical flow characteristics. The feature of the vibro-stimuli is the user feels no vibration when the distance to obstacles keeps constant. Therefore, we considered less discomfort caused by vibro-stimuli generated on the proposed method than the vibro-stimuli based on only static distance. To investigate uncomfortable feelings against the vibro-stimuli of the proposed method, we moved an obstacle closer to eight subjects for five minutes. Then, we evaluated impression for the vibro-stimuli using Semantic Differential scale composed of 15 impression word pairs. As a result, the proposed method gave fewer impressions related to uncomfortable feelings than the vibration based on only static distance. The experiment demonstrated the basic usability of the proposed method.